Pengaruh Variasi Katalis terhadap Ketinggian Api pada Generator HHO - Nurhasan, Muhammad; Ismail, Nova Risdiyanto; Soebiyakto, Gatot (Widyagama University of Malang, 2024)
One of the alternative energies that can be developed is hydrogen. To obtain hydrogen gas by decomposing air compounds (H2O) into hydrogen hydrogen oxygen gas (HHO) through electrolysis. considering the limited energy from the currently available mining materials is increasingly depleted. In order to overcome the above, one solution is to utilize the existence of alternative energy forms by utilizing electrical energy in the form of hydrogen gas stored in H2 which also comes from air (H2O) which can now be used for energy. Through this method, a catalyst is added to improve combustion efficiency in the HHO generator and after research, the addition of 14 grams of catalyst was able to increase energy as seen from the height of the flame 16 mm from the electrolysis process.